2011
DOI: 10.1111/j.1442-200x.2011.03486.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of vitamin D insufficiency in healthy children between 1 and 16 years of age in Turkey

Abstract: Vitamin D insufficiency was found to be very common in the population investigated. The daily calcium intake was below the adequate levels especially in school children. Vitamin D supplementation after the first year of life could be beneficial especially for school children and adolescents. The government must develop public policies for the fortification of milk, milk products, and fruit juices with vitamin D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 47 publications
3
17
0
2
Order By: Relevance
“…In neonates, the lowest rate reported was 53.3% (95% CI: 46.6-66.8) in a study performed in Istanbul by Ozdemir et al [7], and the highest rate was 93% (95% CI: 89.2-95.5) in a study conducted in Izmir by Halicioglu et al [8]. In children, the lowest rate was determined to be 8% (95% CI: 6-10) in a study in Ankara investigated by Akman et al [19], and the highest rate was reported as 82% (95% CI: 79.1-84.6) in a study in Trabzon conducted by Karaguzel et al [15] In adults, the lowest rate determined was 34%, observed in a study in İstanbul performed by Buyukuslu et al [29], and the highest rate was 91%, reported by Bozkurt et al in a study carried out in Ankara (Fig. 2-7).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In neonates, the lowest rate reported was 53.3% (95% CI: 46.6-66.8) in a study performed in Istanbul by Ozdemir et al [7], and the highest rate was 93% (95% CI: 89.2-95.5) in a study conducted in Izmir by Halicioglu et al [8]. In children, the lowest rate was determined to be 8% (95% CI: 6-10) in a study in Ankara investigated by Akman et al [19], and the highest rate was reported as 82% (95% CI: 79.1-84.6) in a study in Trabzon conducted by Karaguzel et al [15] In adults, the lowest rate determined was 34%, observed in a study in İstanbul performed by Buyukuslu et al [29], and the highest rate was 91%, reported by Bozkurt et al in a study carried out in Ankara (Fig. 2-7).…”
Section: Resultsmentioning
confidence: 95%
“…In a study performed on adolescent girls in Turkey, Hatun et al [14] found a rate of deficiency of vitamin D of [18]. Akman et al [19] found that there was vitamin D deficiency and inadequacy of 8% and 25.5%, respectively, in healthy children aged 1-16. Table 3 displays the results obtained from studies of adults.…”
Section: Children and Adolescentsmentioning
confidence: 99%
“…Because vitamin D has a positive influence on calcium balance for building bone and attaining peak bone mass, vitamin D deficiency or insufficiency can contribute to BMD deficit [22]. The prevalence of 25-hydroxyvitamin D (25-OH-D) insufficiency is reported to be 14-49% in the general population and was reported to be between 33.5% and 40% in healthy Turkish children and adolescents in two recent studies [23,24,25,26]. In a recent study of 484 childhood cancer survivors, 17.6% of whom had leukemia, Choudhary et al reported a prevalence of 29% of 25-OH-D insufficiency, and the risk factors for 25-OH-D insufficiency were race, pubertal status, and seasonality [27].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence studies on vitamin D deficiency and/or insufficiency in the Turkish population, especially among prepubertal children over 3 years of age, are relatively scarce (9). The aim of this study was to determine the frequency of deficiency and insufficiency of vitamin D in a sample of Turkish children and adolescents and to investigate the factors associated with low vitamin D status.…”
Section: Introductionmentioning
confidence: 99%